2005
DOI: 10.1111/j.1365-2672.2005.02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale production and liquid formulation of Rhodotorula minuta, a potential biocontrol agent of mango anthracnose

Abstract: Aims: To develop a pilot-plant fermentation process for the production of the yeast Rhodotorula minuta, to be used as a biocontrol agent of mango anthracnose, using a low-cost culture medium. To develop a stable liquid formulation that preserve high viability of the yeast stored at 4°C. Methods and Results: Keeping constant the volumetric power input, a fermentation process was scaled-up from shake flasks to a 100 l bioreactor. Preharvest applications of the yeast resulted in postharvest anthracnose severity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 30 publications
1
29
0
2
Order By: Relevance
“…Results indicated that a shelf life of approximately 7 months could be obtained without a significant loss in viability or efficacy when C. sake cells were grown in a sorbitol-modified medium and then stored in an isotonic solution of trehalose. In another pilot-scale study, production of a liquid formulation of Rhodotorula minuta was evaluated (77). The yeast was formulated at 10 9 CFU/ml in a phosphate buffer solution, with the addition of glycerol (20%) and xanthan (0.5%).…”
Section: Exposure To Stress During Productionmentioning
confidence: 99%
“…Results indicated that a shelf life of approximately 7 months could be obtained without a significant loss in viability or efficacy when C. sake cells were grown in a sorbitol-modified medium and then stored in an isotonic solution of trehalose. In another pilot-scale study, production of a liquid formulation of Rhodotorula minuta was evaluated (77). The yeast was formulated at 10 9 CFU/ml in a phosphate buffer solution, with the addition of glycerol (20%) and xanthan (0.5%).…”
Section: Exposure To Stress During Productionmentioning
confidence: 99%
“…Almost all of the Rhodotorula are non-toxic (Patiño-Vera et al, 2005;Arras et al, 1999). In the present study, the acute oral toxicity test was verified, and Rhodotorula No.BY1109 was safe (Data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Isotonic, liquid formulations of C. sake CPA-1 have been reported to be a suitable alternative to solid formulations (Abadias et al, 2003b;Torres et al, 2003). Liquid formulations have also been tested with R. minuta (Patiño-Vera et al, 2005), C. laurentii (Liu et al, 2009), and P. anomala (Melin et al, 2011).…”
Section: Formulationmentioning
confidence: 99%
“…In general, liquid-phase cultures are used for bacteria and yeasts and solid-phase cultures are used for most fungi. Optimized mass production systems have been described for some postharvest biocontrol agents, including bacteria such as P. agglomerans CPA-2 (Costa et al, 2001), P. agglomerans PBC-1 (Manso et al, 2010) and B. subtilis CPA-8 (Yánez-Mendizábal et al, 2012b), yeasts such as C. sake CPA-1 (Abadias et al, 2003a,b), A. pullulans (Mounir et al, 2007), and Rhodotorula minuta (Patiño-Vera et al, 2005), and fungi such as Penicillium frequentans 909 (De Cal et al, 2002), and Epicoccum nigrum (Larena et al, 2004).…”
Section: Mass Production and Fermentationmentioning
confidence: 99%